2008
DOI: 10.1128/iai.01236-07
|View full text |Cite|
|
Sign up to set email alerts
|

Coinfection withHeligmosomoides polygyrusFails To Establish CD8+T-Cell Immunity againstToxoplasma gondii

Abstract: CD8؉ T-cell immunity is important for long-term protection against Toxoplasma gondii infection. However, a Th1 cytokine environment, especially the presence of gamma interferon (IFN-␥), is essential for the development of primary CD8؉ T-cell immunity against this obligate intracellular pathogen. Earlier studies from our laboratory have demonstrated that mice lacking optimal IFN-␥ levels fail to develop robust CD8 ؉ T-cell immunity against T. gondii. In the present study, induction of primary CD8؉ T-cell immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
5
28
1
Order By: Relevance
“…Consistent with this observation, the frequency of IFNγ positive cells among tetramer-binding CD8 T cells is markedly decreased in coinfected mice (Figure 1B, C and D). In addition, the overall incidence of IFNγ-producing CD8 T cells is also depressed by helminth coinfection (Figure 1B), recapitulating the effects seen by Khan and colleagues(18). …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with this observation, the frequency of IFNγ positive cells among tetramer-binding CD8 T cells is markedly decreased in coinfected mice (Figure 1B, C and D). In addition, the overall incidence of IFNγ-producing CD8 T cells is also depressed by helminth coinfection (Figure 1B), recapitulating the effects seen by Khan and colleagues(18). …”
Section: Resultssupporting
confidence: 82%
“…Khan and colleagues have previously shown that when mice are first infected with H. polygyrus 7 days prior to live T. gondii cyst challenge, polyclonal CD8 T cells fail to respond by IFNγ production (18). Nevertheless, it was unclear whether this defect reflected a helminth-imposed inhibition of cytokine production or a complete blockade in the priming and activation of T. gondii -reactive CD8 T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, for many chronic infections (and tumors [18]), the central (LN) generation of protective Th1 immunity may be sufficient to control infection but local IL-4-rich tissue microenvironments prevent their recruitment and limit anti-microbial function [30]. This may be particularly destructive in the setting of co-infection [30], [32], [67], [68], [69], [70], [71]. Understanding the molecular events that are negatively regulated by IL-4 will be essential for the design of novel therapeutics that target chronic infection by inhibiting IL-4's control of immunity in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…At later stages the T. gondii -specific CD4 + T cell response recovers whereas the CD8 + response remains disrupted (Khan et al, 2008). In line with this, other studies have shown that prior infection with H. polygyrus induced suppression of IL-12 dependent differentiation of effector CD8 + T cells as well as IFN-γ production against T. gondii .…”
Section: Introductionmentioning
confidence: 99%